2018
DOI: 10.1039/c7an01571b
|View full text |Cite|
|
Sign up to set email alerts
|

Chemical analysis in saliva and the search for salivary biomarkers – a tutorial review

Abstract: A review of the uses of saliva biomarkers, detection methods and requirements for new biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 228 publications
(92 reference statements)
0
94
0
Order By: Relevance
“…sAA is considered to be a sensitive biomarker of stress-related changes that reflect the activity of the sympathetic nervous system (SNS) [30]. Most patients with BMS experience chronic pain and have a poorer quality of life than do healthy individuals [9].…”
Section: Discussionmentioning
confidence: 99%
“…sAA is considered to be a sensitive biomarker of stress-related changes that reflect the activity of the sympathetic nervous system (SNS) [30]. Most patients with BMS experience chronic pain and have a poorer quality of life than do healthy individuals [9].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the levels of thiobarbituric acid reacting substances, (15) testosterone, DHEA (Dehydroepiandrosterone), progesterone, and estradiol (16) were artifactually increased by the use of a cotton-based collection material. In contrast, glutathione (17) and sIgA (secretory Immunogloblin A) (16) levels were reduced by cotton. The use of a polypropylene-based material lowered the cortisol levels in samples.…”
Section: Discussionmentioning
confidence: 95%
“…It was concluded that salivary cortisol can be analyzed for a sensitivity of 1 ng/mL using the microfluidic line-free mass sensor. Saliva is attracting increasing attention as a biofluid that can be used as a source of biological indicators, not just of oral diseases [ 34 ] but also of general systemic disease precipitated by stress [ 35 , 36 ]. Analysis of salivary hormones such as cortisol would be medically useful.…”
Section: Resultsmentioning
confidence: 99%